TelePresence in Rural Medical Education: A Mixed Methods Evaluation. (10th February 2014) - Gray, Katherine; Krogh, Kristian; Newsome, David; Smith, Victoria; Lancaster, Donald; Nestel, Debra
Abstract : In response to rural health workforce shortages, universities and training providers offer rural and remote clinical placements. This has led to development of educational methods to counter the barriers of distance. In this emerging field, recent improvements in technology have provided solutions including the use of sophisticated videoconferencing systems such as the Cisco TelePresence model CTS-500. This paper evaluates the use of TelePresence in diverse medical education activities using a mixed methods design—questionnairesn = 60, individual interviewsn = 33, and observed practice of activitiesn = 22 . TelePresence was found to be beneficial to learning and teaching and superior to other systems participants had used. In particular, the audiovisual quality, resulting intimacy, convenience, and ease of use facilitated teaching and learning, while the fixed camera and poorly arranged physical environment were found to be limitations. The system is best suited for small group activities. Clinical skills-based activities are viable. It is recommended that technical support be available during setup and use and a picture-in-picture mode be included and improved integration of office suite software to provide a joint workspace for display of presentations, images, editing or annotation of documents, and file sharing.